Nuclear accumulation of seven in absentia homologue-2 supports motility and proliferation of liver cancer cells - Malz, Mona; Aulmann, Antje; Samarin, Jana; Bissinger, Michaela; Longerich, Thomas; Schmitt, Sabrina; Schirmacher, Peter; Breuhahn, Kai (International journal of cancer, 2012)
Stability of many tumor-relevant proteins is partly mediated by E3 ligases, which determine substrate specificity within the ubiquitin system. Recent data demonstrated that increased nuclear expression of the E3 ligase seven in absentia homologue (SIAH)-1 in human hepatocarcinogenesis supports tumor cell proliferation and migration. To define whether closely related SIAH-2 synergizes with protumorigenic SIAH-1, we systematically analyzed expression, localization and functional relevance of SIAH-2 in human hepatocellular carcinoma (HCC). Nuclear accumulation of SIAH-2 is detectable in more than 60% of all HCCs and correlates with tumor progression, cell proliferation and distant metastasis. An inverse correlation between nuclear SIAH-1 and SIAH-2 was detected, suggesting independent mechanisms for nuclear enrichment. Inhibition of nuclear SIAH-2 by RNAi in HCC cell lines reduced proliferation as well as lateral tumor cell motility and transmigration; however, combined knock down of both SIAH-1 and SIAH-2 did not further amplify biological effects compared to single gene inhibition. Reduction of SIAH-2 expression sensitizes HCC cells to the treatment with different cytostatic drugs, demonstrating that SIAH-2-targeting approaches may increase the response of HCC cells to conventional chemotherapy. Together, these data show that SIAH-2—as described for SIAH-1—accumulates in nuclei of HCC cells where it supports tumor growth and tumor cell dissemination. Because the nuclear pattern of SIAH-2 differs in HCC tissues from the SIAH-1 pattern and because the inactivation of SIAH-2 is not compensated by SIAH-1, the specific inhibition of SIAH-2 (especially in combination with other drugs) represents a promising therapeutic strategy for HCC.
Gesehen am 12.10.2018